2006
DOI: 10.1002/marc.200600436
|View full text |Cite
|
Sign up to set email alerts
|

Facile and Efficient One‐Pot Transformation of RAFT Polymer End Groups via a Mild Aminolysis/Michael Addition Sequence

Abstract: Summary: The trithiocarbonate end groups of polymers prepared by RAFT polymerization are converted into colorless and stable thioethers in a one‐pot process that combines aminolysis of the trithiocarbonate functions and Michael addition of the resulting thiols to α, β‐unsaturated carbonyl derivatives. This post polymerization procedure, which is carried out under mild conditions to near quantitative conversion, is described in the case of a telechelic poly(N‐isopropylacrylamide) sample bearing isobutylsulfanyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
221
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 207 publications
(224 citation statements)
references
References 28 publications
2
221
0
1
Order By: Relevance
“…C Compounds not used as RAFT agents directly but served as precursors to other RAFT agents. [370] Poly(dimethylsiloxane) macro-RAFT agent DMAM [370] DMAM-b-HEA [370] 188 [371,372] [371][372][373] 189 [374] C [374] 190 [286] NIPAM [286] St [286] (NIPAM-b-St) [286] St-b-NIPAM [286] (Continued) [286] St [286] (NIPAM-b-St) [286] St-b-NIPAM [286] 192 [375] …”
Section: S S S O Hn Possmentioning
confidence: 99%
See 2 more Smart Citations
“…C Compounds not used as RAFT agents directly but served as precursors to other RAFT agents. [370] Poly(dimethylsiloxane) macro-RAFT agent DMAM [370] DMAM-b-HEA [370] 188 [371,372] [371][372][373] 189 [374] C [374] 190 [286] NIPAM [286] St [286] (NIPAM-b-St) [286] St-b-NIPAM [286] (Continued) [286] St [286] (NIPAM-b-St) [286] St-b-NIPAM [286] 192 [375] …”
Section: S S S O Hn Possmentioning
confidence: 99%
“…[117] Several groups have found that disulfide formation can be prevented if the thiol formed can be allowed to react in situ. [117,130,373,479,480] For example, end-group reduction can…”
Section: Aminolysis/hydrolysis/ionic Reductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This removal was conducted by aminolysis, as described by Qiu and Winnik [65]. It was expected that the hollow spheres obtained after the aminolysis show approximately the same molecular weight as before, as the polymer material stays unaltered and the RAFT-core is assumed to be negligibly small compared to the polymer material surrounding it.…”
Section: Removal Of the Raft-core By Aminolysismentioning
confidence: 99%
“…As such, RAFT offers an attractive, and convenient, route to telechelic (co)polymers simply via the use of functional RAFT agents. 47 In addition, the thiocarbonylthio end-groups are easily modified postpolymerization to a variety of species including cleavage to a thiol, typically with a primary or secondary amine, 5,48,49 cleavage to a thiolate, 50,51 thermolysis to an ene, 52,53 or radicalinduced reduction to a saturated species with, for example, Bu 3 SnH. 54 Importantly, the presence of the reactive thiol, or thiolate, at the x chain terminus allows for further modification reactions to be performed via the versatile thiol-ene chemistry.…”
Section: Introductionmentioning
confidence: 99%